FRENCH SPORTS PR-TEXTS IN THE TRANSLATION ASPECT (BASES ON THE EXAMPLE OF THE FOOTBALL PRESS) - A.A. Salkhenova; I.A. Fedorova; L.G. Karandeeva (Многоязычие в образовательном пространстве, 2024)
Today, preservation of the nation’s health through sports is becoming a priority in the development of many countries. The sports industry has gained a phenomenal mass appeal, which involves representatives of different languages and cultures into international sports cooperation. The paper is devoted to one of the particular problems in translation – the analysis of Russian translations of French texts about football taken from the French sports press. The relevance of the research is conditioned by the need to study the methods of translating French PR texts into Russian, since they are, on the one hand, of great interest from the standpoint of language theory and, on the other hand, they are an important component of translation practice. For any nation, football has become an integral part of the cultural, social and even political life of society. It is important to recall that the final of the football tournament within the framework of the Summer Olympic Games in Paris will be held in 2024. In connection with this event, translations of sports PR texts will be widely distributed and will present an undeniable value. Moreover, the study of such messages in different languages sheds light on cultural differences as well as on the mentality of native speakers. The aim of the study is to identify the specific features of translating sports texts from French into Russian, taking the football press as an example. Research materials are presented by 200 texts selected by a continuous sampling method from the French football press over the past five years; the methods of communicative analysis and linguistic stylistic text analysis were employed. The results obtained allowed us to see the main features of the translation of PR texts and determine the most effective and productive ways of their transfer into Russian. The practical significance of this work is determined by the fact that the analysis contains recommendations for future translators who are faced with the need to translate PR texts into Russian; it can serve as a useful material for the teachers who train translators, or for current translators working in the field of sports.